Penerapan Sistem Satu Arah (SSA) pada Ruas Jalan Raya Serpong - Muncul Kota Tangerang Selatan dengan Program Vissim - Diartama, Luh Gede Melyarista; Naibaho, Pio Ranap Tua (Jurnal Talenta Sipil, 2025)
South Tangerang City is a rapidly growing city, resulting in an increase in traffic volume that is out of proportion to road capacity. This situation causes congestion on the Serpong-Muncul Highway, especially during rush hour. This stretch of road is lined with schools and serves as a vital access point from Bogor City to South Tangerang. Therefore, traffic engineering is needed to determine traffic performance before and after the implementation of the one-way system, and to determine its effectiveness. Analysis is carried out by calculating based on the Indonesian Road Safety Guidelines (PKJI 2023) on conditions before (divided into 2 segments) and after the implementation of the One-Way System and by using the Vissim program. Based on the results of traffic performance analysis on conditions before the implementation of the One-Way System on segment 1 (2/2 TT) the degree of saturation was 0.88 so the LOS was E. The results of the analysis for segment 2 (4/2 TT) the degree of saturation was 0.80 so the LOS was D. While after the implementation of the One-Way System the degree of saturation was 0.72 so the LOS was C. And the results of the analysis with the vissim program showed a decrease in front of Junior High Scool 8, the original LOS was B to A. While in front of Senior High School 2 the original LOS was C to A. Due to the decrease in service levels, the implementation of the One-Way System is effective in reducing congestion and improving performance on the Serpong – Muncul Highway in South Tangerang City.